(untitled) (Malaysian Journal of Learning and Instruction, 2017)
Purpose - Citation is vital in academic writing but particularly challenging for novice writers who use English as a second or foreign language. While much is known about citations types and functions, scarce knowledge is available about what makes citing a complicated procedure. Hence, this study explores the difficulties in citing and integrating information from academic sources into the literature review chapter of PhD proposals. Methodology - The study, which falls under New Rhetoric studies, involved conducting individual discourse-based interviews with six male Arab doctoral students who were selected purposefully from the Information Technology department of a Malaysian public university. The participants’ literature review chapters were employed in a stimulated recall to retrieve their inner perceptions when writing their PhD proposals. Hand analysis, mind mapping, and visual mapping were used in the analysis of the data. Multiple codes were initially obtained and further reduced to form four major themes and several sub-themes. Findings - The findings revealed that challenges in citation included addressing the credibility of information in published sources, adopting a stance toward the citations, insufficient knowledge about using citations, and second language difficulties. Significance - The findings highlight that EFL Arab students lacked both awareness of using citations and advanced skills in academic writing. Consequently, the study has pedagogical implications in that it points to a need to enhance EFL Arab students’ skills in citing, evaluating, and writing academically. This could be probably achieved through developing discipline-specific teaching materials that take into consideration the different practices of citation in various academic disciplines.